Using educational tools and technological media to ensure the quality of training and education in the LMD system - ramdane.boukhors,; bousakra ahmed, (sports creativity, 2025)
This study aims to clarify the importance of utilizing educational tools and technological media in training and education, emphasizing their close relationship with information technology and ensuring the quality of education and training at various levels within higher education under the new system. It also presents the design and production guidelines for educational tools, the principles for selecting teaching and learning tools, and methods for evaluating them. Introduction: The challenges facing the world due to scientific openness through communication and information networks necessitate that university educational institutions focus on modern teaching and learning methods that consider several variables (objectives, content, student level, and educational tools). The use of teaching and learning tools at various levels of higher education within the LMD (License-Master-Doctorate) system is of great importance in achieving the goals of university education reforms. To achieve this, professors must be highly skilled and possess the expertise and competencies to use and select these tools according to educational situations. This will enable them to provide opportunities for ongoing professional development and training for students, ensuring their preparation and training to a high level of competence. Educational tools are a key element of educational communication, enhancing the effectiveness of the learning process, achieving its objectives, and resolving its problems. Educational media have received considerable attention in developed countries due to their impact on educational outcomes, as they ensure active interaction between the learner and the learning environment. This analytical study will attempt to demonstrate the importance of utilizing and employing educational media in guaranteeing the quality of education and higher education, emphasizing their close relationship with educational technology, presenting the design and production guidelines for educational media using the ASSURE model as an example, and outlining the principles for selecting and evaluating educational media.